2009
DOI: 10.1063/1.3153953
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and structural properties of sputtered HfO2 layers

Abstract: Magnetron sputtered HfO2 layers formed on a heated Si substrate were studied by spectroscopic ellipsometer (SE), x-ray diffraction (XRD), Fourier transform infrared (FTIR), and x-ray photoelectron spectroscopy (XPS) depth profiling techniques. The results show that the formation of a SiO x suboxide layer at the HfO2 /Si interface is unavoidable. The HfO2 thickness and suboxide formation are highly affected by the growth parameters such as sputtering power, O2 /Ar gas ratio during sputtering, sputtering time, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 28 publications
5
41
0
Order By: Relevance
“…The results infer that there existed a very thin perfect Hf-oxide layer, later Si-Si bonds are detected even before Si suboxide layer is reached and then Si substrate is reached. Since Si-Si bonds were measured just before Si-oxide is reached, it can be realized that highly reactive sputtered Hf atoms consume some of the oxygen atoms from the underlying SiO 2 to form hafnium-oxide by leaving Si-Si bonds behind [3]. Our results also confirm what Yamamoto et al revealed with their experiment that the oxygen radicals oxidize the Hf metal more selectively than Si substrate [11].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The results infer that there existed a very thin perfect Hf-oxide layer, later Si-Si bonds are detected even before Si suboxide layer is reached and then Si substrate is reached. Since Si-Si bonds were measured just before Si-oxide is reached, it can be realized that highly reactive sputtered Hf atoms consume some of the oxygen atoms from the underlying SiO 2 to form hafnium-oxide by leaving Si-Si bonds behind [3]. Our results also confirm what Yamamoto et al revealed with their experiment that the oxygen radicals oxidize the Hf metal more selectively than Si substrate [11].…”
Section: Resultssupporting
confidence: 81%
“…oxide film gives the idea of causing elementally active sputtered Hf radicals decompose the native SiO 2 to form elemental silicon atom and oxygen molecule and/or atom explicitly. As a result, the oxygen gained from the native SiO 2 oxide is used to form HfO 2 while leaving unbonded elemental Si atoms or Si-suboxide behind [3].…”
Section: Xps Depth Profiling Spectrum For Chemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research groups have studied interfacial layer formations in Si/HfO 2 structure during both fabrication and annealing. Thermodynamically driven SiO 2 /Si formation at Si/HfO 2 interface is usually observed on the substrate side of HfO 2 [4]. This may degrade the performance of device.…”
Section: Introductionmentioning
confidence: 99%
“…5 Important film properties as well as interfacial structure affecting especially electrical properties including dielectric constant and refractive index of the grown film, depend on the growth parameters as well as the initial thin film constitution. [6][7][8] Therefore, it should be noted that the applied physical conditions on thermally grown SiO 2 must be well controlled through the whole stages during further processing steps in order to improve its dielectric properties.…”
Section: Introductionmentioning
confidence: 99%